Natural Productivity, Morphometrics and Seasonal Distribution of Caulerva Racemosa - Raza’i Tengku Said (EDP Sciences, 2021)
Caulerva racemosa seaweed is a superior commodity with both ecological and socio-economical benefits. It is technologically developed into different products which include antioxidants, antibiotics, medicinal ingredients, cosmetics as well as other organic products and also used conventionally as food ingredients for human’s consumption. Meanwhile, the presence of C. racemosa is observed to decrease as the exploitation rate is one of the factors affecting its stock in the nature. Changes in environmental conditions contribute majorly to its availability in aquatic ecosystems. Furthermore, natural factors in the form of seasonal changes that cause fluctuations in water dynamics are the main focus affecting its lifespan. The results showed that C. racemosa growth parameters, which include percentage cover, productivity, together with morphometrics, failed to be significantly affected by seasonal changes. Meanwhile, the highest percentage cover was found during the northern monsoon, which has an average value of 37.99 ± 7.67 (Average±STDEV), while the lowest was during the eastern monsoons with 28.03 ± 9.09 respectively. The best morphometric size was during the northern monsoon with a tallus dimension of 0.25 with an average of 0.201 ± 0.03 and length of 0.825 ± 0.16, a stolon length of 2.09 with an average of 1.95 ± 0.08, 9 stolon grains with an average of 8 ± 0.2. However, the grain diameter, as well as the biomass, was 0.85 gr and 0.054 gr with an average of 0.825 ± 0.22 gr and the grain biomass was with an average of 0.040 ± 0.01 and 0.041 gr with the best average stolon was 0.031 ± 0.01 g in the western season. The results showed that C. racemosa, which grows up in different seasons, having its highest productivity during the northern season and the lowest one was during the eastern season with an average value of 0.439 ± 0.36 kg/m2 as well as 0.326 ± 0.37 Kg/m2, respectively